2002
DOI: 10.1038/sj.bjc.6600559
|View full text |Cite
|
Sign up to set email alerts
|

ALA and ALA hexyl ester induction of porphyrins after their systemic administration to tumour bearing mice

Abstract: The use of synthetic lipophilic molecules derived from 5-aminolevulinic acid (ALA) is currently under investigation to enhance cellular ALA penetration. In this work we studied the effect of systemic administration to mice of the hexyl ester of ALA (He-ALA) on porphyrin tissue synthesis as compared to ALA. In most normal tissues as well as in tumour, He-ALA induced less porphyrin synthesis than ALA after its systemic administration either intravenous or intraperitoneal, although explant organ cultures exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 30 publications
(23 reference statements)
2
38
0
Order By: Relevance
“…However, the mechanical dispersion of skin to obtain the required single-cell suspension was not possible, and an enzymatic dispersion would have required a moderate incubation period, thus not allowing determination of fluorescence 3 h after ALA administration. Here, a recent study by Perotti et al (2002) is noteworthy, which examined porphyrin synthesis using spectrofluorometry following ALA administration and found a similar tumour to liver ratio (1.3) to that reported here (1.1). At the same time, they obtained a tumour to skin ratio of 2.94.…”
Section: Resultssupporting
confidence: 83%
“…However, the mechanical dispersion of skin to obtain the required single-cell suspension was not possible, and an enzymatic dispersion would have required a moderate incubation period, thus not allowing determination of fluorescence 3 h after ALA administration. Here, a recent study by Perotti et al (2002) is noteworthy, which examined porphyrin synthesis using spectrofluorometry following ALA administration and found a similar tumour to liver ratio (1.3) to that reported here (1.1). At the same time, they obtained a tumour to skin ratio of 2.94.…”
Section: Resultssupporting
confidence: 83%
“…The fact that porphyrin biosynthesis induced from ALA cream is also delayed, favours the latter hypothesis. Moreover, culturing different tissue explants (tumour, normal skin, SOT, liver, kidney and spleen) exposed to ALA or He-ALA, we found that porphyrin levels from either compounds were similar, supporting the proposal that there are no differences on esterase activity for any tissue (Perotti et al, 2002).…”
Section: Discussionsupporting
confidence: 79%
“…A plethora of 5-ALA esters has been reported with the improved lipophilicity and cell uptake. 27,28 However, most of these molecules still remain considerably toxic and therefore not suitable for systemic administration 13,20 . Furthermore, the unprotected 5-amino group makes the molecule chemically unstable at physiological pH found in bloodstream leading to its degradation and irreversible formation of cyclic dimers that are not able to enter the heme cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Its limited bioavailability and poor pharmacokinetic profile make 5-ALA suboptimal for systemic administration. 13 To overcome these shortcomings, different strategies have been employed. Up to now, making the molecule more lipophilic by esterification of its carboxyl function has provided the most effective solution reducing the dose needed for the optimal PpIX production up to 150-fold.…”
Section: Introductionmentioning
confidence: 99%